Propriedades mecânicas e durabilidade do concreto produzido com agregados reciclados - Murakami, Flavia de Fátima Emi (2024)
The exploration and consumption of mineral aggregates used in concrete, environmental degradation and the generation of construction waste are some of the impacts caused and are increasing with the development of the sector. Recycling is a sustainable alternative for disposing of construction waste, as well as reducing the consumption of natural inputs and helping to reduce environmental impacts. The use of recycled aggregate for concrete production is an alternative and sustainable solution, but there is a fear that concrete dosed using recycled aggregates will be of inferior quality when compared to concrete with natural aggregates, in terms of mechanical, physical and durability performance parameters, and it’s important to limit the quantity and quality of recycled aggregates. Therefore, this experimental program was developed to analyze the mechanical and durability properties of a concrete mix with aggregate produced from construction waste. For this purpose, reference concretes were produced with replacement levels of 10%, 20%, 30% and 40% of natural aggregate with recycled aggregate. Fifty-four 10x20 cm cylindrical test specimens were produced for each mix, to evaluate the performance of recycled aggregate as its replacement content increases. The properties evaluated were: compressive strength, tensile strength by diametrical compression, modulus of elasticity, water absorption by capillarity, water absorption by immersion, void index and specific mass, carbonation depth and ultrasonic pulse velocity. The results showed that it is feasible to use recycled aggregate from construction materials in the production of concrete, considering the mechanical properties and durability. The results obtained indicated a good quality concrete.